Pengaruh Self Efficacy dan Soft Skill terhadap Kesiapan Kerja: Studi Kasus pada Generasi Z di Kabupaten Tasikmalaya - Rima Rohmawati; Nurherawati Nurherawati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The era of globalization and accelerated digital transformation has given rise to increasingly competitive job markets, requiring every individual to possess adequate skills, confidence, and abilities to face professional demands. In this situation, Generation Z, as a productive age group, still faces various obstacles related to job readiness, for example, a lack of confidence in meeting job expectations and a low mastery of non-technical skills required by industry. This research intends to assess the influence of self-efficacy and soft skills on the employment preparedness of Generation Z in Tasikmalaya Regency using quantitative approaches. The sample comprised 100 participants who were chosen using a non-probability sampling technique, specifically purposive sampling. Data collection employed an ordinal-scale questionnaire, and data analysis was conducted using multiple linear regression testing. The findings indicate that self-efficacy has a partial, positive, and significant influence on job readiness. A similar impact is also demonstrated by the soft skills variable, where these non-technical skills are proven to accelerate individual readiness. When tested simultaneously, the combination of self-efficacy and soft skills plays a crucial role in strengthening the job readiness of Generation Z in Tasikmalaya Regency. These findings emphasize that the combination of self-confidence and interpersonal and intrapersonal competencies is the main foundation for facing the world of work. Therefore, this study offers practical implications regarding the urgency of strengthening both aspects through academic pathways, training programs, and stimulating work experiences to produce a Generation Z capable of optimally responding to the dynamics of industry needs.